Attitudes, awareness, and knowledge of Wolbachia-Aedes aegypti technology in Yogyakarta: a survey - B, Jassey; R, Yudhastuti; H B, Notobroto; R, Azizah; D K, Candraning; M R, Ridha; R, Indrayani; L, Sulistyorini; J, Jalaludin; B, Manjang; F I, Permatasari (Institute of Physics, 2024)
In 2014, Yogyakarta initiated the release of male Wolbachia-Aedes mosquitoes as a supplementary measure to vector control efforts, targeting the suppression of Aedes aegypti mosquitoes in designated study areas. Concurrently, with the ongoing expansion of the Randomized Control Trial of Wolbachia in Yogyakarta to encompass broader regions, a household-based survey was conducted between January and June 2024 across two Project Wolbachia study sites. The survey utilized a structured questionnaire to gauge current public sentiments and identify the need for enhanced public messaging and engagement. Factors influencing awareness, attitudes, and knowledge towards Wolbachia-Aedes technology were examined using Pearson’s Chi-square test and binary logistic regression analysis. Among the 1000 respondents, 80.8% reported a Randomized Control Trial of Wolbachia in Yogyakarta awareness. However, the level of detailed knowledge about Wolbachia-Aedes technology was notably lower, indicating significant knowledge gaps that necessitate improved communication and educational efforts to counter misinformation. The survey revealed that prolonged exposure to the project correlated with higher awareness, while higher educational attainment was linked to better knowledge levels. Additionally, younger age groups and individuals with higher education levels demonstrated greater project acceptance. Trust and acceptance levels towards the project were generally high among the population. The public's favorable perception of the project underscores the success of the current public communication strategies and will support the program's future expansion.